Divorce Issues among Spouses in Onitsha North Local Government Area of Anambra State - R.N, Chike (Journal of Home Economics Research, 2024)
The study investigated issues relating to divorce among spouses in Onitsha North Local Government Area (LGA) of Anambra State. Specifically, the study identified causes of divorce in the area; determined perceived effects of divorce on children’s development; and ways of curbing divorce. Three research questions were formulated to guide the study. Descriptive survey research design was used. Population was made up of male and female secondary school teachers in Onitsha North LGA. One hundred and forty (140) married male and female teachers were randomly sampled from the secondary schools in the area.. Questionnaire was used for data collection. Data were analyzed using mean. Findings of the study include: 18 causes of divorce in the area; including bareness/childlessness (X=3.56), husband’s physical abuse on the wife (X=3.90); 19 perceived effects of divorce on development of children aged 11-15 years, including emotional and difficult to handle (X=3.23), usually unhappy, sad and depressed (X=3.32), among others. Other findings are 12 possible ways of curbing divorce in the area, including divorce should not be legalized so that couples will be discourage from ending their marriage (X=3.64), couples should learn to resolve their differences by themselves (X=3.63), and so on. Six recommendations were made, including, among others, that couples should get premarital training from churches and/or other religious organizations before proceeding with the marriage; there should be at least a one to two years period of courtship before marriage.